Upaya Petani Padi Dalam Mengatasi Gagal Panen Di Desa Anjir Pasar Lama, Kecamatan Anjir Pasar, Kabupaten Barito Kuala 2016-2024 - Rahmatullah Rahmatullah; Mansyur Mansyur; Fitri Mardiani; Mohamad Zaenal Arifin Anis (Publikasi Berkala Pendidikan Ilmu Sosial, 2025)
The focus of this research is to analyze the various strategies applied by rice farmers in facing the risk of crop failure due to biotic and abiotic factors. Anjir Pasar Lama Village is an agricultural area that depends on the agricultural sector, especially rice cultivation, as the main source of community livelihood. However, farmers are faced with various challenges, such as pest attacks (tungro), limited access to irrigation water, extreme climate change, and high production costs.This research uses the historical method, including the stages of heuristics (data collection through interviews, observation, document studies, and analysis of object sources), source criticism (external and internal), interpretation, and historiography writing. Data were obtained from key informants, such as rice farmers, community leaders, and village officials, supported by written sources and field documentation. The results show that farmers' efforts include the application of integrated pest control techniques, the use of superior pest-resistant seeds, optimization of the use of modern and traditional agricultural tools, and active participation in training programs organized by the government and related institutions. In addition, the development of irrigation infrastructure and disaster mitigation programs, such as the prevention of land fires, also help improve agricultural resilience. This research is expected to serve as a reference in the formulation of sustainable agriculture policies and strengthening food security in rural areas. The findings also contribute to the development of agrarian history studies, especially related to the dynamics of adaptation of farming communities to environmental and socio-economic challenges.